Anti-Listeria monocytogenes activity of enterocins microencapsulated by ionic gelation - Ibarguren, Carolina (2012)
The encapsulation of enterocins synthesized by Enterococcus faecium CRL1385 through ionic gelation with calcium ions was analyzed. Different enterocins samples were lyophilised and encapsulated using low-methoxyl pectin as the coating material. Lipids present in milk butter were also added to control the release of antimicrobial peptides from the capsules. The morphology of fresh and freeze-dried capsules was examined using light microscopy and scanning electron microscopy, respectively. Antimicrobial activity of encapsulated bacteriocins was assessed against Listeria monocytogenes 01/155 using the agar diffusion technique and direct contact in microplates. The capsules with higher lipid content showed a more spherical and uniform shape. Pathogen inhibition was observed for capsules prepared with different bacteriocin solutions both on solid (halo diameter ¼ 8.5e13.5 mm) and in an aqueous medium (ca. 2 log orders decline in L. monocytogenes viability). The outcomes suggest that bacteriocin encapsulation through ionic gelation can be a potential alternative for the application of these antimicrobial peptides as biopreservatives in food.